Highly controllable direct femtosecond laser writing of gold nanostructures on titanium dioxide surfaces. Issue 35 (23rd August 2017) - Fujita, Y.; Aubert, R.; Walke, P.; Yuan, H.; Kenens, B.; Inose, T.; Steuwe, C.; Toyouchi, S.; Fortuni, B.; Chamtouri, M.; Janssen, K. P. F.; De Feyter, S.; et al.
Abstract : Highly controllable direct femtosecond laser writing of gold nanostructures on titanium dioxide surfaces has been demonstrated. Abstract : A highly reproducible and controllable deposition procedure for gold nanostructures on a titanium dioxide (TiO2 ) surface using femtosecond laser light has been demonstrated. This is realized by precisely focusing onto the TiO2 surface in the presence of a pure gold ion solution. The deposition is demonstrated both in dot arrays and line structures. Thanks to the multi-photon excitation, we observe that the deposition area of the nanostructures can be confined to a degree far greater than the diffraction limited focal spot. Finally, we demonstrate that catalytic activity with visible light irradiation is enhanced, proving the applicability of our new deposition technique to the catalytic field.